2019
DOI: 10.1002/ccd.28585
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of single versus double Perclose devices for transfemoral aortic valve replacement access site closure: Insights from Cleveland Clinic Aortic Valve Center

Abstract: Introduction: Percutaneous femoral access is the preferred access route for transcatheter aortic valve replacement (TAVR). The majority of experienced TAVR centers use two 6F Perclose ProGlide™ devices to close the primary vascular access site, deployed prior to upsizing sheath size with closure completed at the end of the case (the "preclose" approach). A strategy of utilizing a single Perclose device to preclose may have advantages including fewer complications, complexity, and cost, but the safety of this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…First, it is noteworthy that three (6%) patients were treated with femoral stents due to failed hemostasis. This is even higher than the rates with single ProGlide technique reported by Bazarbashi et al 1 Second, patients with severe calcification at the access site were excluded from the study. Therefore, more data are needed on the performance of the device in the calcified vessels.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…First, it is noteworthy that three (6%) patients were treated with femoral stents due to failed hemostasis. This is even higher than the rates with single ProGlide technique reported by Bazarbashi et al 1 Second, patients with severe calcification at the access site were excluded from the study. Therefore, more data are needed on the performance of the device in the calcified vessels.…”
mentioning
confidence: 84%
“…Currently, the Prostar percutaneous vascular surgical system (Prostar XL; Abbott Vascular Inc., Santa Clara, CA) and the PerClose ProGlide closure device (Abbott Vascular Inc., Santa Clara, CA) are the most commonly used VCD for large-bore access with a "preclosure" method. Although the majority of the centers utilize a double device technique, use of a single 6-F ProGlide with an additional AngioSeal device to control the residual bleeding if necessary was also shown to be a safe strategy 1. Although these devices were not designed for large-bore access, some studies found comparable safety of preclose technique compared to surgery.…”
mentioning
confidence: 99%
“…The design of these studies makes their results difficult to interpret. Either only one THV system was investigated 2 or various vascular closure device (VCD) systems, 3 or different second and third generation THV systems 4 . Randomized clinical trials (RCTs) report Valve Academic Research Consortium (VARC)‐2 defined major vascular complications with third‐generation THV ranging from 6 to 7.9% in intermediate risk‐ and from 2 to 3.8% in low risk patient cohorts 5‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that the utilization of a single ProGlide device for preclosing the vascular access site as a strategy may have certain advantages, including reducing the cost of the procedure, decreasing the overall procedure duration, and minimizing of the vascular complications when compared to double ProGlide devices in patients undergoing TAVR 4. In this issue of Catheterization and Cardiovascular Interventions, Bazarbashi et al provided new data on the safety and efficacy of utilizing a single ProGlide strategy for closure during TAVR in comparison to the strategy of preclosing with two ProGlide devices 5.…”
mentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions, Bazarbashi et al provided new data on the safety and efficacy of utilizing a single ProGlide strategy for closure during TAVR in comparison to the strategy of preclosing with two ProGlide devices 5 …”
mentioning
confidence: 99%